Guideline treatment results in regression of atherosclerosis in type 2 diabetes mellitus. (March 2015) - Strang, Aart C; van Wijk, Diederik F; Mutsaerts, Henri JMM; Stroes, Erik SG; Nederveen, Aart J; Rotmans, Joris I; Rabelink, Ton J; Box, Frieke MA
Background: Efficacy of guideline cardiovascular disease prevention regimens may differ between patients with or without type II diabetes mellitus. We therefore compared change in carotid artery wall dimensions in type II diabetes mellitus and non-type II diabetes mellitus patients with a history of a major cardiovascular disease event, using magnetic resonance imaging. Methods: Thirty type II diabetes mellitus patients and 29 age- and sex-matched non-diabetes mellitus patients with a history of stroke or myocardial infarction and a carotid artery stenosis (15%–70%) were included. In all patients, treatment was according to cardiovascular risk management guidelines. At baseline and follow-up, carotid artery vessel wall dimensions were measured using 1.5 T magnetic resonance imaging. Results: After 2 years of follow-up, total wall volume of the carotid artery in type II diabetes mellitus patients decreased by 9.6% ( p  = 0.016). In contrast, stabilization rather than regression of carotid artery wall dimensions was observed in non-diabetes mellitus patients over a 2-year period. Body mass index was identified as a predictor of total wall volume decrease. Conclusions: Guideline treatment arrests atherogenesis in non-diabetes mellitus patients and even decreases vessel wall dimensions in type II diabetes mellitus patients. Baseline body mass index predicts cardiovascular disease prevention efficacy expressed as decrease in total wall volume. These data emphasize the importance of optimal cardiovascular-prevention, particularly in diabetes patients with a high body mass index.